Implementasi dan Persepsi Publik Terhadap SP4N‑LAPOR di Kota Pontianak - Samhaji, Samhaji; Francesco Dennis Anggara (JOPPAS: Journal of Public Policy and Administration Silampari, 2025)
This study aims to analyze the implementation of the public complaint service policy through SP4N-LAPOR in Pontianak City and to understand the meaning of the use of this application for citizens. The method used is a qualitative approach with a phenomenological perspective, employing data collection techniques in the form of in-depth interviews, participant observation, and documentation, with an emphasis on citizens’ experiences and perceptions in using SP4N-LAPOR as a public complaint platform. The results show that the use of SP4N-LAPOR facilitates the submission of public complaints, enhances transparency in public services, and strengthens interaction between citizens and the local government; however, several obstacles remain, including limited user understanding of application procedures, varying response levels among government agencies, and the need for more intensive socialization. In conclusion, the successful implementation of SP4N-LAPOR is influenced by policy socialization, human resource capacity, and the effectiveness of the monitoring system, indicating the need for local governments to improve citizens’ digital literacy, strengthen inter-agency coordination, and enhance responsiveness in following up on public complaints.   Keywords: phenomenology, Pontianak, public complaint services, public policy, SP4N-LAPOR